1988
DOI: 10.1111/j.1445-5994.1988.tb00176.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal Disease in Diabetics—which Patients Have Diabetic Nephropathy and What Is Their Outcome?*

Abstract: From August 1974 to January 1985, 53 patients (26 men; seven Maoris) mean age 45 (SD 15) years, with diabetes mellitus for a mean of 12 (SD nine) years had a renal biopsy and were followed. Indications for biopsy were nephrotic syndrome, proteinuria, renal impairment (five) and hematuria (one). Mean plasma creatinine concentration was 0.22 (SD 0.18) mmol/L and protein excretion 3.4 (SD 2.5) g/24 h. Diabetic nephropathy was demonstrated in 39 patients and significantly associated with retinopathy and insulin de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The contribution of non-diabetic disease in this cohort is unclear. Although the only study involving biopsies in New Zealand found all Maori patients to have diabetic nephropathy [21], local clinical experience has led to biopsies no longer being routinely taken in South Auckland because of the low yield of non-diabetes-related disease among Polynesians.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of non-diabetic disease in this cohort is unclear. Although the only study involving biopsies in New Zealand found all Maori patients to have diabetic nephropathy [21], local clinical experience has led to biopsies no longer being routinely taken in South Auckland because of the low yield of non-diabetes-related disease among Polynesians.…”
Section: Discussionmentioning
confidence: 99%
“…For at least the last two decades, there has been suggestions that a 2 M is increased in certain forms of diabetes mellitus, particularly in the presence of microangiopathic complications (6)(7)(8). This triad of three recognized situationsFhigh a 2 M in the nephrotic syndrome (5), high a 2 M in diabetic renal disease (9,10), and association of the nephrotic syndrome with diabetes mellitus (11)(12)(13)Fthus warrants further investigation using a 2 M as a tool for diagnosis and monitoring of diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Incidence rates and hazard ratios for end-stage renal disease (ESRD) among Maori diabetes patients have not been estimated previously. Available studies on nephropathy among Maori diabetes patients have limitations because they were cross-sectional, looked at prevalence [3,4], included dialysis and transplant registry patients only [5][6][7][8], or included existing renal disease patients only [9]. The Waikato Regional Diabetes Service (WRDS) provides specialist diabetes services and retinal screening for people in the area covered by the Waikato District Health Board (DHB).…”
Section: Introductionmentioning
confidence: 99%